Evidence for plant traits driving specific drought resistance. A community field experiment (Environmental and Experimental Botany, 2012)
Drought is known to be a major bottleneck for woody-community recruitment. The species-speciﬁc resistance to drought and factors involved in its variation are of special interest to forecast community fate. We performed an experiment under natural ﬁeld conditions from winter 2006 to end summer 2008 to investigate the structural responses of woody saplings to nine combinations of light (three habitats differing in plant cover:forest, shrubland, and open) andwater (three climate scenarios: drier, current and wetter summers). Our working hypothesis is that plant strategies to cope with drought are determined by habitat characteristics and/or variation of plant traits, and that these different strategies may determine community composition and dynamics. Eight woody species with different life forms and successional stages (trees, mid-successional shrubs, and pioneer shrubs) were selected for the comparison, including therefore species representative of the entire woody community. We explored drought resistance at the population level (DS), the relations of the different morphological traits to DS, and the potential importance for plants of inter-speciﬁc trade-offs. DS ranged from 0% to 99% for the different species, depending on the habitat. Some structural traits were found to be related to DS: positively with total biomass and leaf mass ratio (LMR) and negatively with leaf area-root mass ratio (LARMR). Contrary to previous studies, the present work revealed no evidence of trade-offs, such as survival in forest vs. growth in open, or growth in forest vs. growth in open. Accordingly, some species with low DS values (Acer opalus and Pinus sylvestris) would be threatened under the future climate conditions, while species having structural characteristics to increase their resistance under expected dry years in coming decades (i.e., high LMR and total biomass or low LARMR, such as Quercus ilex and the shrub Cytisus scoparius) might enhance their recruitment probabilities. Thus, species-speciﬁc plant traits, and their effect on DS, may ﬁlter future community assemblages.

Sporadic rainy events are more critical than increasing of drought intensity for woody species recruitment in a Mediterranean community. (Oecologia, 2012)
The understanding of the impact of extreme climatic events under a global climate change scenario is crucial for the accurate forecast of future plant community dynamics. We have experimentally assessed the effect of drier and wetter summer conditions on the recruitment probabilities and the growth of seedlings from eight woody species representative of the most important functional groups in the community, pioneer shrubs, mid-successional shrubs and trees, across the main habitats in the study area (open habitat, shrubland, and forest). Our hypothesis proposes that wet summer conditions would represent a good opportunity for tree species regeneration, enhancing both forest maintenance and expansion. A drier summer scenario, on the other hand, would limit forest regeneration, and probably hinder the colonization of nearby habitats. We found a habitat effect on the emergence, survival, and final biomass, whereas different climate scenarios affected seedling survival and biomass. A wet summer boosted growth and survival, whereas greater drought reduced survival only in some cases. These results were modulated by the habitat type. Overall, shrub species presented higher survival and growth and were less affected by more severe drought, whereas some tree species proved to be extremely dependent on wet summer conditions. We conclude that the reduction in frequency of wet summers predicted for the coming decades in Mediterranean areas will have greater consequences for species recruitment than will increased drought. The different response of the species from the various functional groups has the potential to alter the composition and dominance of future plant communities.

Consistent pattern of habitat and species selection by post-dispersal seed predators in a Mediterranean mosaic landscape - Matías, Luis; Mendoza, Irene; Zamora, Regino; Mat, Luis (Plant Ecology, 2009)
There is still little information on effects of habitat degradation on post-dispersal seed predation at the landscape scale. The aim of this study was to determine the inﬂuence of habitat degradation and seed species on the variability of post-dispersal seedpredation rate. Experimental seed removal was investigated in six Mediterranean woody plant species, four trees (Pinus sylvestris, Quercus ilex, Acer opalus ssp. granatense, and Sorbus aria) and two shrubs (Berberis vulgaris and Crataegus monogyna), in an extensively used mosaic landscape on the Sierra Nevada massif (SE Spain). Seed depots were distributed over 2 years in ﬁve differently degraded landscape units, each one with three plots: shrubland; native forest; and dense, cleared and fenced reforestation stands. Predation was the highest in native forest, shrubland, and fenced reforestation, and the lowest in dense and cleared reforestation stands, being partially due to a positive correlation between shrub cover and post-dispersal seed predation. However, the main factors driving post-dispersal seed predation were intrinsic to seeds, as species preference explained most of the variance in our model for predation. The plant-species ranking was Quercus[ Pinus[Sorbus[Berberis[Acer[Crataegus, the dominant tree species being the most depredated. These ﬁndings are novel because they suggest for the ﬁrst time that species-selection patterns by postdispersal seed predators tended to remain constant through both study years in all habitats comprising a mosaic landscape, whether native forest, reforestation stands or successional shrubland.
The following values have no corresponding Zotero field: publisher: Springer Netherlands
Keywords: Degraded habitats; Field experiment; Land use change; Logistic regression; Predator preference; Sierra Nevada

Consistent pattern of habitat and species selection by post-dispersal seed predators in a Mediterranean mosaic landscape (Plant Ecology, 2009)
There is still little information on effects of habitat degradation on post-dispersal seed predation at the landscape scale. The aim of this study was to determine the inﬂuence of habitat degradation and seed species on the variability of post-dispersal seedpredation rate. Experimental seed removal was investigated in six Mediterranean woody plant species, four trees (Pinus sylvestris, Quercus ilex, Acer opalus ssp. granatense, and Sorbus aria) and two shrubs (Berberis vulgaris and Crataegus monogyna), in an extensively used mosaic landscape on the Sierra Nevada massif (SE Spain). Seed depots were distributed over 2 years in ﬁve differently degraded landscape units, each one with three plots: shrubland; native forest; and dense, cleared and fenced reforestation stands. Predation was the highest in native forest, shrubland, and fenced reforestation, and the lowest in dense and cleared reforestation stands, being partially due to a positive correlation between shrub cover and post-dispersal seed predation. However, the main factors driving post-dispersal seed predation were intrinsic to seeds, as species preference explained most of the variance in our model for predation. The plant-species ranking was Quercus[ Pinus[Sorbus[Berberis[Acer[Crataegus, the dominant tree species being the most depredated. These ﬁndings are novel because they suggest for the ﬁrst time that species-selection patterns by postdispersal seed predators tended to remain constant through both study years in all habitats comprising a mosaic landscape, whether native forest, reforestation stands or successional shrubland.